Stylizing Genderlect Online for Social Action: A Corpus Analysis of 'BIC Cristal for Her' Reviews. (January 2016) - Ray, Brian
This article introduces the concept of stylization and illustrates its usefulness for studying online discourse by examining how writers have employed it in order to parody sexist products such as BIC Cristal for Her, using genderlect in order to introduce dissonance into and reframe patriarchal discourse. A corpus analysis of 671 reviews, written from August through October 2012, confirmed a dramatically higher presence of lexical items and adjectives often stereotyped as feminine, compared to a reference corpus of other parody reviews, as well as the GloWbe corpus housed at Brigham Young University. A qualitative analysis shows the stylized use of these features, and how they contribute to the construction of personas that are intended to mock the sexism inherent in BIC's advertising. This analysis hopes to encourage more attention to how stylization functions in emerging online genres.